A Chinese Prescription Yu-Ping-Feng-San Administered in Remission Restores Bronchial Epithelial Barrier to Inhibit House Dust Mite-Induced Asthma Recurrence - Bao, Kaifan; Yuan, Weiyuan; Zhou, Yijing; Chen, Yanyan; Yu, Xuerui; Wang, Xiaoyu; Jia, Zhirong; Yu, Xi; Wang, Xiaotong; Yao, Lu; Wang, Siqi; Xu, Yifan; et al. (Frontiers in Pharmacology, 2020)
Clinically, the treatments against asthma like β2 agonist focus on controlling the symptoms rather than inhibiting recurrence radically. This study aims to evaluate the efficacy and mechanism of a potent Chinese prescription Yu-Ping-Feng-San (YPFS) against asthma recurrence. We here established an optimized house dust mite (HDM)-induced asthma recurrence mice model with typical asthmatic responses such as significantly augmented airway hyperresponsiveness (AHR), elevated serum IgE, pulmonary type 2 cytokines IL-5 and IL-13 levels, pathological changes including thickening bronchial wall, inflammatory infiltration of lung tissue, etc. Moreover, all typical asthmatic pathological features were prominently alleviated by YPFS applied during remission phase ahead of second elicitation, which was even more effective than three different types of medications dexamethasone, montelukast and salbutamol, which were commonly applied in clinical practice, administered during recurrence phase. Besides, we found that desmoglein 1 (DSG1) remained deficient when asthmatic responses regressed whereas tight junction (TJ) claudin 1 (CLDN1) or adherin junction (AJ) E-cadherin restored spontaneously. In vitro, DSG1 interference resulted in increased thymic stromal lymphopoietin (TSLP) secretion, and epithelial barrier compromise evidenced by significantly elevated transepithelial electrical resistance (TEER) and increased 4-kDa FITC-dextran influx. YPFS could downregulate TSLP production and restore HDM-induced DSG1 deficiency and barrier destruction, which was further reversed by shDSG1. Collectively, administration of YPFS in remission prominently alleviated HDM-induced asthma relapse by restoring DSG1 and decreasing TSLP overexpression, which might be the key factors contributing to chronic asthma relapse. Our data not only demonstrated the pivotal role of DSG1 in asthma pathogenesis, but also provided a novel and potent therapeutic strategy against chronic asthma.